Is agile the latest management fad? A review of success factors of agile transformations. Issue 4 (12th October 2020) - Naslund, Dag; Kale, Rahul
Abstract : Purpose: Agile is the new popular management change method and agile has lots of momentum. Management consulting firms are promoting agile via articles and newsletters. While history does not repeat itself, it often rhymes, and thus agile will probably be a successful change effort in some organizations. On the other hand, there is a high probability that agile will not deliver the expected results for most organizations. History reveals that about two-thirds of the change efforts are deemed unsuccessful – regardless of the actual change method. In this paper, we present the results of a systematic literature review on agile and we compare and contrast it with other similar organizational change methods. The purpose of this paper is to explore what one may learn from the history of the earlier change methods in terms of how organizations may succeed in their agile efforts. Design/methodology/approach: The paper is based on a structured literature review of the agile concept – including agile transformation, and with a specific focus on critical success factors. Findings: In addition to presenting the state of the art on agile in general, we identify, structure and categorize critical success factors (CSF) for agile. From the 13 categories, we form three clusters, which constitute a 3P framework (purpose, process and people). We also compare and contrast the CSF literature regarding agile with CSFs for organizational change in general. history indicates that most organizational change efforts are not successful. Based on the framework and the discussion, we provide recommendations to hopefully increase the probability of successful agile implementations. Originality/value: Given the relative novelty or at least the renewed interest in agile, a structured literature review of the current status of this "new" method provides value as it may help organizations and managers to not repeat old mistakes – once again.